A202 BIOCHEMICAL PROFILE IN 68 PRIMARY BILIARY CHOLANGITIS (PBC) SUBJECTS HAVING AN INADEQUATE RESPONSE TO URSODEOXYCHOLIC ACID. (1st March 2018) - Boudes, P F; Bacon, B; Varga, M; Choi, Y; Steinberg, A; Turner, T; Swain, M
Abstract: Background: Ursodexoxycholic acid (UDCA) is the first line treatment for PBC. However, up to 40% of subjects have an inadequate response characterized by a persistent elevation of Alkaline Phosphatases (AP). Aims: Herein, we describe a number of additional biochemical abnormalities in PBC subjects having an inadequate response to UDCA. Methods: Sixty-eight subjects with a confirmed diagnosis of PBC and a persistent elevation of AP (>1.67xULN) despite treatment with UDCA for at least a year were screened for a phase 2 intervention study (NCT02609048/EudraCT2015-002698-39). The mean age was 55 years old and 65 subjects were females (96%). The % of subjects with abnormal values and mean parameters values relative to the upper limit of normal (ULN) were assessed for the following: AP, γ-glutamyl transferase (GGT), 5' nucleotidase (5'N), transaminases (AST/ALT), Bone specific AP (BSAP), total-cholesterol (TC), LDL-C, HDL-C, total protein, total bilirubin (TB) and its fraction (direct and indirect), and albumin. The presence of lipoprotein X (LpX) in serum was assessed and a complete blood count was performed. Multiple linear correlations were explored. Results: In addition to AP elevation, the most frequently elevated parameters in these subjects were GGT (97%), BSAP (90%), 5'N (76%), TC (75%), HDL-C (71%), AST (54%), ALT (47%), LDL-C (44%), direct bilirubin (35%), total protein (19%), and TB (16%). No subjects had LpX detected despite some having HDL-C cholesterol that reached 3-fold ULN. There were strong correlations between AP and BSAP, AST, GGT and 5'N (all correlation coefficients ≥0.6 and p< 0.001). There was no correlation between AP and HDL-C. Conclusions: The frequency of BSAP elevation and its strong correlation with AP were unexpected and could indicate that osteopenia is more prevalent in this population. The elevation of direct bilirubin was twice more frequent than the elevation of TB and could constitute a more sensitive prognostic marker. GGT was quantitatively more elevated than AP. The HDL-C elevation, which is known in PBC, can however reach unusual levels that are rarely seen in other conditions. The HDL-C increase did not correlate with the other markers of cholestasis, and it mechanism is unclear. LpX was not detected in any patients. The frequent increase in total protein is probably a consequence of the polyclonal increase in immunoglobulin M. Funding Agencies: CymaBay Therapeutics